Pengaruh Model Pembelajaran Project Based Learning dan Problem Based Learning dengan Self Confidence Terhadap Hasil Belajar Atletik Lari Jarak Pendek - safitri, rahmita; Alnedral, Alnedral; Gusril, Gusril; Wahyuri, Asep Sujana; Ockta, Yovhandra (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2023)
The purpose of this study is to see the impact of three factors, namely the Project Based Learning Model, the Problem Based Learning Learning Model, and the Level of Confidence (Self Confidence), on learning achievement in the discipline of Short Distance Running Athletics among students of State Junior High School 23 Pekanbaru. The method used in this study is a quasi-experiment with a quantitative approach. This study involved two sample groups, namely the experimental group and the control group, consisting of a total of 40 students. Data is collected through observations, tests, and documentation. The results of the data analysis showed several important findings as follows: First, the PjBL Learning Model has a significant impact on the learning achievement of Short Distance Running Athletics in students. Second, the PBL Model also has a significant impact on the learning achievement of Short Distance Running Athletics in students. Third, Self Confidence also has a significant influence on the learning achievement of Short Distance Running Athletics in students. Conclusion, the PjBL Learning Model, PBL Learning Model, and Self Confidence together contribute significantly to the achievement of Short Distance Running Athletics learning in students. Keywords: Learning Model Project Based Learning, Problem-Based Learning, Self Confidence, and Learning Outcomes